ASSESSMENT OF KNOWLEDGE AND PRACTICE REGARDING MENSTRUAL HYGIENE AMONG UNIVERSITY STUDENTS - TALIB , S; LAL , B; BATOOL , S; TESNEEM , SS; JABEENN , R (Biological and Clinical Sciences Research Journal, 2024)
Menstrual hygiene is a critical aspect of women’s reproductive health, particularly among university students who may face challenges due to cultural taboos and inadequate knowledge. In Pakistan, discussions around menstruation are often stigmatized, leading to gaps in awareness and practices that can affect women’s health and academic performance. Objectives: This study aimed to assess the knowledge and practices regarding menstrual hygiene among female university students in Lahore, Pakistan, to identify gaps and inform future educational interventions. Methods: A descriptive cross-sectional study was conducted over three months at Superior University, Lahore. A total of 300 female students aged 18–25 years were selected using Slovin’s formula. Data were collected through a structured questionnaire covering demographic information and specific questions on menstrual hygiene knowledge and practices. Responses were measured on a Likert scale ranging from "strongly disagree" to "strongly agree." Data analysis was performed using SPSS version 22, employing descriptive statistics and inferential analyses. Results: The participants were nearly equally divided between married (49.7%) and single (50.3%) students, with a slight majority being postgraduates (52%). Awareness of various menstrual products was limited, with only 36.4% of participants expressing adequate knowledge. While 55.6% recognized the importance of regularly changing menstrual products, 22% remained neutral. Proper disposal practices were known by 39%, and only 50.3% acknowledged the importance of hand hygiene. Comfort in discussing menstrual hygiene with peers was moderate, with 44.7% expressing comfort. A significant proportion (59.7%) supported the inclusion of menstrual hygiene education in university programs, and 62% advocated for the provision of free menstrual products on campus. Conclusions: The study revealed significant gaps in knowledge and practices related to menstrual hygiene among university students in Pakistan. Cultural stigma and inadequate education contribute to these deficiencies. There is a critical need for comprehensive menstrual hygiene education programs within universities, along with institutional support to provide resources and foster an environment that encourages open dialogue. Addressing these issues is essential for improving women’s health outcomes and promoting gender equity in educational settings.